Oxidative rancidity development in reformed and cooked chicken meat - Nur Adila Basari
Oxidative rancidity is a major cause of quality deterioration in cooked chicken meat products stored at refrigeration temperatures. Butylated Hydroxytoluene (BHT), a synthetic antioxidant normally used to control lipid oxidation in foods has been shown to have several health issues and is banned in several European countries and Japan. Two experiments were conducted to evaluate the effectiveness of red palm olein (RPOo) and BHT to retard lipid oxidation and to determine vitamin E and carotenes levels in reformed and cooked chicken meat during storage at 0±4°C. In the first experiment, boneless chicken leg meat was mixed with either chicken fat or with palm shortening containing varied amounts of palm olein, palm kernel oil, palm stearin, RPOo (0, 22.5 and 45%) and BHT (0, 50 and 10 ppm). The meat batter was stuffed in test tubes, cooked to an internal temperature of 75°C and st red for 60 days at 0±4°C. In a follow-up experiment, the chicken meat batter was prepared with chicken fat or with palm shortening containing varied amounts of palm olein, palm kernel oil, palm stearin and RPOo (0, 22.5 and 45%), stuffed in high density polyethylene (HDPE) plastic casing, cooked to an internal temperature of 75° C and stored 120 days at 0±4°C. The concentrations of thiobarbituric acid reactive substances (TBARs), tocopherols, tocotrieonols, alpha- and beta-carotene in the cooked batter during storage were monitored. In both experiments, the pal shortening was formulated to achieve slip melting point similar to that of chicken fat. The results of the first experiment showed that at day 1, TBARs value of the meat batter were in the range of 0.68 to 0.78 mg MDAlkg. The batter formulated with chicken fat as the main source of fat had the highest TBARs value (p <0.05). The TBARs values of the other formulations ranged from 0.68 to 0.73 were not significantly different. At day 30, the TBARs values of the batter formulated with chicken fat and palm shortening without RPOo or BHT were 3.32 and 2.42 mg MDA/kg respectively. Addition of 22.5 and 45% of RPOo in the palm shortening reduced the TBARs values to 1.84 and 1.57 mg MDAlkg respectively. For the same storage period, the TBARs values for samples with 50 and 100 ppm BHT were 2.24 and 1.89 mg MDAlkg respectively. In experiment two, the TBARs values at day 30 were 3.71, 2.65, 2.28 and 2.13 mg MDAlkg for meat batters formulated with chicken fat, palm shortening without RPOo and palm shortening with 22.5 and 45% RPOo respectively. At the end of the storage period, vitamin E level in the cooked chicken meat with palm shortening containing 22.5 and 45% RPOo were 269.39 and 298.11 mg/kg respectively compared to 30.58 mg/kg for the batter formulated with chicken fat. At the same time, total ar t ne level was 77.82 mg/kg in the samples with 22.5% RPOo and 141.67 mg/kg for batter with 45% RPOo; almost 70 percent of vitamin E and 75 percent of carotenes were retained. Addition of 22.5 and 45% RPOo in palm shortening has been shown to reduce oxidative rancidity and increased vitamin E and carotenes levels in cooked chicken meat batter during storage at 0±4°C.